The impact of simulated 3x3 tournament on vertical jump force-time metrics in national team male basketball players - Cabarkapa, Dimitrije; Aleksic, Jelena; Krsman, Darko; Cabarkapa, Damjana V.; Philipp, Nicolas M.; Fry, Andrew C. (Frontiers in Physiology, 2024)
With innovative portable force plate systems being widely implemented for lower-body neuromuscular performance assessment in an applied sports setting and the existing gap in the scientific literature regarding player performance during in-game competitive scenarios, the purpose of the present study was to compare changes in countermovement vertical jump (CVJ) performance pre-post a simulated 3x3 basketball tournament. Seven current or former members of a 3x3 national basketball team volunteered to participate in the present investigation. Upon completing standardized warm-up procedures, athletes stepped on a uni-axial force plate system sampling at 1000 Hz and performed three maximal-effort CVJs with no arm swing. Then, the athletes proceeded to play a simulated 3x3 basketball tournament composed of two consecutive games, separated by a 15-minute rest interval. Immediately following the completion of the second game, the identical CVJ testing procedures were repeated. Paired sample t-tests were used to examine pre-post-tournament differences in nineteen CVJ performance metrics (p<0.05). The results reveal that force-time metrics during both eccentric and concentric phases of the CVJ remain relatively unchanged pre-post simulated 3x3 basketball tournament. However, multiple force-time metrics within the eccentric phase of the CVJ changed by 12.1-19.1% (e.g., eccentric peak power and peak velocity, eccentric duration), suggesting that the eccentric phase of CVJ might be responsive to performance stimulus to a greater extent than the concentric phase. Overall, these findings further support the importance of comprehensive CVJ analysis when intending to measure changes in neuromuscular performance.